Get ready! : - Harris, Joseph (McGraw-Hill, 2000)
With standardized, state-mandated testing starting as early as the first grade and continuing through high school, parents are concerned that their children may not be able to perform at grade level. Developed by professionals, here is the first and only grade-specific test preparation series geared toward parent and child, including expert tips for optimizing children's test performances.